Gregarious Flowering of Bamboos in North-east India - Need for Intensive Management - Kishwan, Jagdish; Goyal, A. K. (Indian Forester, 2006)
The gregarious flowering of muli bamboos is expected to occur in the NE States of India in the next two years, after it completes its 48 year cycle. The administration, public representatives, the people and all other stakeholders have initiated preemptive action to deal with this ecological phenomenon keeping in view the past experience of happenings due to gregarious flowering of bamboos in the North-East India especially in Mizoram. The State Governments in the North-East as well as Government of India have prepared a detailed Action Plan for managing this natural calamity having wider social and economic implications with utmost caution, alert and preparedness. However, the problem can be effectively managed only with proactive action by various agencies in the State Governments and the cooperation of various ministries/ departments at the GoI levels, civil society and the people. Adequate funding from various sources in the States and assistance from the GoI is essential to help mitigate the impact of this problem. A foolproof contingency plan is necessary for mitigating the intensity of the problem, taking preventive action in avoiding the fire hazards, outbreak of famine, providing relief to the people in the form of food grains and medical help in the event of outbreak of an epidemic. This natural calamity can be converted into an opportunity for the welfare of the people of these States by adequately utilizing the large quantity of raw material which would be available in the form of flowered bamboos. The various agencies like TIFAC, Ministry of Science and Technology, GoI; Indian Plywood Industries Research and Training Institute, Bangalore etc. are providing necessary technical know-how for value addition.